Implementation and Validation of Online Tidal Analysis - Basith, Abdul; Dondiarta, Ghani Yanuargo (Jurnal Geospasial Indonesia, 2025)
Tidal harmonic analysis extracts tidal components to understand regional tides that generally conducted using commercial or non-commercial software that needs to be installed on the user's local device. Currently there is still no online harmonic analysis service for tidal data, only an online tidal prediction service. Auto Tidal Pro is developed to perform harmonic analysis and prediction online and is designed to automate the process. It is built using the least square method and Java programming language for harmonic analysis and tidal prediction programs. This study aims to present the results of the development of the online tidal data analysis system called Auto Tidal Pro and its validation. Validation is conducted by comparing the results of harmonic analysis and predictions from the LP-Tides software and observational data. The tidal observational data used is from Balikpapan station. The validation results show that the amplitude component values are close to the LP-Tides results, but the phase values still show some differences. The RMSE value of the harmonic analysis results with Auto Tidal Pro ranges from 0.032-0.17 m, while the RMSE of LP-Tides results is 0.12 m. The MSL difference in about 0.012-0.004m. Auto Tidal Pro prediction produce wave patterns that are almost identical to the observational data and the  LP-Tides predictions. The prediction RMSE gives values between 0.08-0.16 m, and the correlation between Auto Tidal Pro's predictions with observational data and LP-Tides predictions ranges from 0.930816-0.990809. In general, Auto Tidal Pro can be an alternative for tidal harmonic analysis and prediction.